2012
DOI: 10.1371/journal.pone.0040174
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Spatio-Temporal Dynamics of Supragranular Activity in the Rat Somatosensory Cortex in Response to Stimulation of the Paws

Abstract: We employed voltage-sensitive dye (VSD) imaging to investigate the spatio-temporal dynamics of the responses of the supragranular somatosensory cortex to stimulation of the four paws in urethane-anesthetized rats. We obtained the following main results. (1) Stimulation of the contralateral forepaw evoked VSD responses with greater amplitude and smaller latency than stimulation of the contralateral hindpaw, and ipsilateral VSD responses had a lower amplitude and greater latency than contralateral responses. (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 83 publications
(138 reference statements)
8
10
0
Order By: Relevance
“…The longer latency of our optical signal is thus attributed to this experimental situation. Morales-Botello et al (2012) obtained hind-limbevoked cortical optical responses with a latency of 23 ms, much shorter than ours and in good agreement with that of the evoked potentials. While their recording procedures were similar to ours, one of the main differences was the choice of VSD; they used RH1691.…”
Section: The Evoked Response Detected By Optical Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The longer latency of our optical signal is thus attributed to this experimental situation. Morales-Botello et al (2012) obtained hind-limbevoked cortical optical responses with a latency of 23 ms, much shorter than ours and in good agreement with that of the evoked potentials. While their recording procedures were similar to ours, one of the main differences was the choice of VSD; they used RH1691.…”
Section: The Evoked Response Detected By Optical Methodssupporting
confidence: 89%
“…It differs among sensory cortices; 220 mm/s in the visual cortex, 380 mm/s in the auditory cortex (Song et al, 2006;Wanger et al, 2013) and much smaller values were reported in the somatosensory cortex. Morales-Botello et al (2012) reported spreading velocities of 80 mm/s and 120 mm/s for the hind-limb and fore-limb responses, respectively. Petersen et al (2003) reported spreading velocities of 60 mm/s and 33 mm/s in the barrel cortex (in the barrel cortex the velocity differs according to the direction of propagation; the former along the row and the latter along the arc).…”
Section: Propagating Velocitymentioning
confidence: 99%
“…This expansion of the FLS cortex into the FLM cortex is not completely unexpected, because in physiological conditions cortical responses to forepaw stimuli propagate both toward the HLSM cortex and toward the FLM cortex, as recently measured with voltage-sensitive dye imaging in rats (Morales-Botello et al, PLoS ONE 2012). The reorganization was not limited to regions of FLM cortex adjacent to forelimb sensory cortex.…”
Section: Discussionsupporting
confidence: 61%
“…Similarly, hindpaw stimuli also evoked small responses in the forepaw cortex (Table 1). These observations are consistent with our previous results6710.…”
Section: Resultssupporting
confidence: 94%
“…Interestingly, these increased responses to forepaw stimuli are not observed only in the hindpaw cortex, which is deafferented by the thoracic spinal cord injury, but also in the forepaw cortex, which would be classically considered as non-deafferented. However, in control animals the hindpaw cortex does display small responses to forepaw stimuli6910, suggesting that the loss of input from the hindpaw produces a partial deafferentation also of the forepaw cortex. If this interpretation is correct, an increment in the responses evoked in the forepaw cortex by forepaw stimuli should be observed not only after central hindpaw deafferentation due to spinal cord injury, as in our previous studies, but also immediately after peripheral hindpaw deafferentation due to nerve injury.…”
mentioning
confidence: 99%